Faroese pilot whaling in a cosmopolitan war: A study on political ontologies, multinaturalism and eurocentrism - Heradóttir Andreassen, Katarina (Culture and History: Student Research Papers, 2025)
This article examines the controversy surrounding Faroese pilot whaling (grindadráp) through the lens of political ontologies, encapsulating how differing worldviews shape the interpretation of pilot whaling in the Faroe Islands, and what implications these have for local-global dynamics and cultural sovereignty. By comparing Faroese perspectives of subsistence, cultural sovereignty, and sustainable local governance with activist framings of animal rights and global ecological protection, the article highlights the clash between multinaturalist and eurocentric “One World World” ontologies. The findings suggest that the conflict extends beyond debates on sustainability, revealing deeper struggles over authority and the right to define ethical relations with nonhuman life.